Tribute to Alberto Wagner De Reyna, Dr., philosopher and humanist - Wagner Grau, Patrick (2013)
The ontological analysis of Heidegger’s thought about nothing, lead us to consider the cliff, whichstands proud from the void spring towards the sky, surpassing the Void of itself. The cliff showsmultiple cracks in its own structure and those cracks are an integral part of his being. Similarly, thehuman being raises from the deep Void transcending and rising into the infinite, having as part of itsown being the nothing (with small letter) that could be equated with the cracks of being. Faith beatsVoid (with capital letter), integrating the ontological voids and allow transcendence of man towardsthe supreme.